Infrastructure Deficits and Their Impact on Learning Conditions in Elementary Schools in Madagascar - Michel, Rakotoniriana Noelisoa Jean; Emynorane, Ralaivao Hanginiaina; Sulla, Razafitahindraza Erica Feyzine; Ratna, Hangivola Emyblonde (Pendagogia: Jurnal Pendidikan Dasar, 2025)
This study aims to examine infrastructure deficits and their impact on learning conditions in elementary schools in the Haute Matsiatra region of Madagascar. Using a qualitative research approach, data were collected through classroom observations and semi-structured interviews with 45 key informants, including teachers, school principals, local education officials, and parents. The findings reveal that many schools operate under poor physical conditions characterized by inadequate classrooms, overcrowding, insufficient teaching materials, and limited access to sanitation facilities. These conditions negatively affect students’ concentration, participation, and academic performance, while also reducing teacher effectiveness and motivation. The study further highlights significant disparities between rural and peri-urban schools, where unequal distribution of resources reinforces educational inequities. Although local communities attempt to address some infrastructural gaps through collective efforts, their contributions remain limited without sufficient institutional and governmental support. Data analysis using thematic coding revealed recurring patterns linking poor infrastructure to weakened teaching and learning processes. The study concludes that improving school infrastructure is essential for enhancing educational quality and equity in the region.